Success in Introductory Programming: What Works? - Porter, Leo; Guzdial, Mark; McDowell, Charlie; Simon, Beth (Communications of the ACM, 2013)
The article discusses computer science education as of August 2013, arguing that research supports instruction methodologies such as pair programming, media computation, and peer instruction. Topics include the computer science requirements of the Georgia Institute of Technology and the potential social and collaborative aspects of computer science.